Determinant Factors Associated with the Incidence of Varicose Veins among Pregnant Women - Putri, Wanda Dwi; Agustin, Agustin; Anggraini, Rima Berti (Genius Journal, 2025)
Introduction: Pregnancy causes physiological changes that may increase the risk of varicose veins, which can lead to discomfort and complications for both mother and fetus. Objective: This study aims to identify factors associated with the incidence of varicose veins in pregnant women at Selindung Primary Health Center in 2025. Method: This study used a quantitative method with a descriptive analytical design using a cross-sectional approach, which involved cross-tabulating the dependent and independent variables. The sample in this study was 110 women who underwent pregnancy check-ups at the Selindung Community Health Center. The sample size for this study was 60. Data analysis used the chi-square test with a 95% confidence interval. Result: The results of this study were to determine the relationship between the dependent variable, namely the incidence of varicose veins, and the independent variables. The statistical test results for the family history variable yielded a p-value of 0.001, the pregnancy gravida variable yielded a p-value of 0.005, the gestational age variable yielded a p-value of 0.012, the prolonged standing habit variable yielded a p-value of 0.026, and the harmonic contraception variable yielded a p-value of 0.001. Conclusion: The study concluded that the most influential factor was family history, with a POR value of 7.540. This is because genetic factors can influence the strength and elasticity of the vein walls, which are then exacerbated by physiological changes during pregnancy. Therefore, there is a significant association between family history and the incidence of varicose veins in pregnant women at the Selindung Primary Health Center in 2025.